Rational 2-functions are abelian - Müller, Luis Felipe (Communications in number theory and physics, 2021)
We show that the coefficients of rational 2-functions are contained in an abelian number field. More precisely, we show that the poles of such functions are poles of order one and given by roots of unity and rational residue.